PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA GAIA SHOP - Suryawardana, Edy; Putri, Febrita Valenia; Rizkiana, Citra; Indriyanti, Irma Satya (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to examine and analyze the influence of Product Quality and Price on Purchasing Decisions with Customer Satisfaction as an Intervening variable at Gaia Shop. The dependent variables used in this research are Purchase Decision (Y), Customer Satisfaction (Z) while the independent variables used are Product Quality (X1) and Price (X2). The sample in this study was 96 respondents. The sampling technique uses non-probability sampling with the criteria that the respondent is 17 years old and has purchased and used Gaia Shop products at least once. The analytical methods used are Convergent Validity, Discriminant Validity, Composite Reliability, Inner Model. The results of the research conducted show that Product Quality and Price have a positive and significant effect on Customer Satisfaction, the Product Quality variable has a positive and significant effect on Purchasing Decisions, the Price variable has a positive and insignificant effect on Purchasing Decisions, the Product Quality variable has a positive and significant effect on Decisions Purchasing through Customer Satisfaction, and the Price variable have a positive and significant effect on Purchasing Decisions through Customer Satisfaction.